Literature Review: Effectiveness Treatment of Scabies in Peranakan Etawa Goat with Subcutaneous and Topikal E Methods - Al Iman, Annastasya Putri Aulia; Lastry, Lastry; Putri, V. Acsyi Sih Pangesti; Hidayah, Nurulia (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
One of the parasitic diseases that often infect goats was scabies caused by Sarcoptes scabiei. This review was conducted with the aim of determining the handling of scabies cases that infect Peranakan Etawa (PE) goats, through 2 treatment methods, namely subcutaneously with anti-parasite injection of ivomec at a dose of 0.025 mL/kg of livestock body weight, injection every 10 days. Topical treatment with amitraz using a dose of 10 ml of amitraz homogenized with 1,250 mL of water, applied directly to the scabbed skin using cotton, rubbing amitraz every 1 week. The parameters observed were the length of healing time from the two treatment methods given and the level of effectiveness of subcutaneous and topical treatment.